Midkine Mediates Intercellular Crosstalk between Drug-Resistant and Drug-Sensitive Neuroblastoma Cells In Vitro and In Vivo. (3rd September 2013) - Chu, Fei; Naiditch, Jessica A.; Clark, Sandra; Qiu, Yi-Yong; Zheng, Xin; Lautz, Timothy B.; Holub, Janette L.; Chou, Pauline M.; Czurylo, Michael; Madonna, Mary Beth
Abstract : Resistance to cytotoxic agents has long been known to be a major limitation in the treatment of human cancers. Although many mechanisms of drug resistance have been identified, chemotherapies targeting known mechanisms have failed to lead to effective reversal of drug resistance, suggesting that alternative mechanisms remain undiscovered. Previous work identified midkine (MK) as a novel putative survival molecule responsible for cytoprotective signaling between drug-resistant and drug-sensitive neuroblastoma, osteosarcoma and breast carcinoma cells in vitro . In the present study, we provide further in vitro and in vivo studies supporting the role of MK in neuroblastoma cytoprotection. MK overexpressing wild type neuroblastoma cells exhibit a cytoprotective effect on wild type cells when grown in a co-culture system, similar to that seen with doxorubicin resistant cells. siRNA knockdown of MK expression in doxorubicin resistant neuroblastoma and osteosarcoma cells ameliorates this protective effect. Overexpression of MK in wild type neuroblastoma cells leads to acquired drug resistance to doxorubicin and to the related drug etoposide. Mouse studies injecting various ratios of doxorubicin resistant or MK transfected cells with GFP transfected wild type cells confirm this cytoprotective effect in vivo . These findings provide additional evidence for the existence of intercellular cytoprotective signals mediated by MK which contribute to chemotherapy resistance in neuroblastoma.